God and Existence from Aquinas' Perspective and its Relationship with the Originality of Existence and Argument of the Righteous in Transcendent Wisdom - mahdi meshgi (حکمت اسرا, 2022)
One of the methods of religious thinkers in explaining and proving religious and theological propositions is the use of philosophical propositions. Many Islamic and Christian theologians have used this method. Among the Islamic theologians, Ibn Sina, Khawaja Nasir, Allama Hali, and Sadr alMuta’allehin did. One of the Christian thinkers who put philosophy at the service of religious beliefs is Thomas Aquinas. He, who has used the works of Ibn Rushd and Ibn Sina a lot in philosophy, tries to use the philosophical issue of Existence and Essence and provide an accurate explanation of the existence of God Almighty and creation. He considers existence and God as one and considers God as the actuality or act of existence and believes that creatures receive existence from God. Although Aquinas builds his philosophical foundations with the philosophy of Aristotle and the interpretation of Ibn Rushd and Ibn Sina but with one interpretation, the requirement of his theory can be considered as approaching the originality of existence and the argument of the truthful. The present article uses analytical-descriptive method to analyze his theory of existence and God from the book of “Existence and Essence” and expresses its implications.